Antimicrobial Usage Factors and Resistance Profiles of Shiga Toxin-Producing Escherichia coli in Backyard Production Systems From Central Chile - Pavez-Muñoz, Erika; González, Camilo; Fernández-Sanhueza, Bastián; Sánchez, Fernando; Escobar, Beatriz; Ramos, Romina; Fuenzalida, Verónica; Galarce, Nicolás; Arriagada, Gabriel; Neira, Víctor; Muñoz-Aguayo, Jeannette; Flores-Figueroa, Cristian; et al. (Frontiers in Veterinary Science, 2021)
Shiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen and important cause of foodborne disease worldwide. Many animal species in backyard production systems (BPS) harbor STEC, systems characterized by low biosecurity and technification. No information is reported on STEC circulation, antimicrobial resistance (AMR) and potential drivers of antimicrobial usage in Chilean BPS, increasing the risk of maintenance and transmission of zoonotic pathogens and AMR generation. Thus, the aim of this study was to characterize phenotypic and genotypic AMR and to study the epidemiology of STEC isolated in BPS from Metropolitana region, Chile. A total of 85 BPS were sampled. Minimal inhibitory concentration and whole genome sequencing was assessed in 10 STEC strain isolated from BPS. All strains were cephalexin-resistant (100%, n=10), and five strains were resistant to chloramphenicol (50%). The most frequent serotype was O113:H21 (40%), followed by O76:H19 (40%), O91:H14 (10%) and O130:H11 (10%). The stx1 type was detected in all isolated strains, while stx2 was only detected in two strains. The Stx subtype most frequently detected was stx1c (80%), followed by stx1a (20%), stx2b (10%) and stx2d (10%). All strains harbored chromosomal blaAmpC. Principal component analysis shows that BPS size, number of cattle, pet and horse, and elevation act as driver of antimicrobial usage. Logistic multivariable regression shows that recognition of diseases in animals (p = 0.038; OR= 9.382; 95% CI: 1.138 – 77.345), neighboring poultry and/or swine BPS (p = 0.006; OR = 10.564; 95% CI: 1.996 – 55.894), visit of Veterinary Officials (p = 0.010; OR = 76.178; 95% CI: 2.860 – 2029.315) and close contact between animal species in the BPS (p = 0.021; OR = 9.030; 95% CI :1.385 – 58.888) increase significantly the risk of antimicrobial use in BPS. This is the first evidence of STEC strains circulating in BPS in Chile, exhibiting phenotypic AMR, representing a threat for animal and public health. Additionally, we identified factors acting as drivers for antimicrobial usage in BPS, highlighting the importance of integration of these populations into surveillance and education programs to tackle the potential development of antimicrobial resistance and therefore the risk for ecosystemic health.